2020
DOI: 10.33860/jik.v14i2.132
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Edukasi Stimulasi Tumbuh Kembang terhadap Kemampuan Deteksi Dini Tumbuh Kembang Anak Usia 0-5 Tahun oleh Orangtua

Abstract: Stimulasi merupakan salah satu faktor yang mempengaruhi perkembangan anak. Hal ini seringkali oleh sebagian orangtua mengabaikannya akibat ketidaktahuan orangtua tentang cara dan pentingnya memberikan stimulasi anak sejak usia dini. Tujuan penelitian untuk mengetahui pengaruh edukasi stimulasi tumbuh kembang terhadap kemampuan deteksi dini tumbuh kembang anak usia 0-5 tahun oleh orangtua. Penelitian ini merupakan penelitian kuantitatif dengan desain Quasy Eksperiment Desaign dengan rancangan one group pretest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 5 publications
0
6
0
15
Order By: Relevance
“…Based on the results of interviews with cadres, it was stated that not all posyandu cadres knew the technicalities of monitoring developmental disorders in children. due to lack of information and the presence of new cadres who have not been trained (Ludyanti et al, 2022) This is proven to have an influence on the results of the knowledge assessment before and after being given Health Education (Cumayunaro et al, 2020;Lisnawati et al, 2022;Nurul Abidah & Novianti, 2020) The research results showed that more than half of the respondents had poor knowledge, 26 (52%), whereas after being given Health Education, 38 people (76%) experienced an increase in the good category. If we look at the Wilcoxon test, we get a p-value of 0.000 < 0.05, then Ho is rejected and Ha is accepted, meaning that there is a difference in the level of knowledge of respondents before and after being given health education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of interviews with cadres, it was stated that not all posyandu cadres knew the technicalities of monitoring developmental disorders in children. due to lack of information and the presence of new cadres who have not been trained (Ludyanti et al, 2022) This is proven to have an influence on the results of the knowledge assessment before and after being given Health Education (Cumayunaro et al, 2020;Lisnawati et al, 2022;Nurul Abidah & Novianti, 2020) The research results showed that more than half of the respondents had poor knowledge, 26 (52%), whereas after being given Health Education, 38 people (76%) experienced an increase in the good category. If we look at the Wilcoxon test, we get a p-value of 0.000 < 0.05, then Ho is rejected and Ha is accepted, meaning that there is a difference in the level of knowledge of respondents before and after being given health education.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances, height increases with age. Linear growth that is not appropriate for age can reflect a condition of malnutrition over a long period of time, resulting in stunting in children (Nurul Abidah & Novianti, 2020). Stunting describes chronic malnutrition status during growth and development since Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil kajian di RA Ar-Rahman Tanjung Pauh Mudik Kabupaten Kerinci menunjukkan bahwa ada pengaruh lama interaksi dan stimulasi pada anak terhadap perkembangan motorik anak usia prasekolah dan tidak ada pengaruh umur, pendidikan, dan pekerjaan ibu terhadap perkembangan motorik pada anak usia 3-4 tahun [12]. Pemberian edukasi stimulasi tumbuh kembang anak oleh orangtua dapat meningkatkan kemampuan orangtua dalam memberikan stimulasi tumbuh kembang sejak dini yang akan berdampak positif seperti meningkatkan perkembangan bahasa dan memori anak, kesiapan anak dalam sekolah dan membantu anak untuk memaksimalkan potensi dalam hidupnya [13]. Terapi bermain juga bisa menjadi salah satu upaya untuk menstimulasi perkembangan anak.…”
Section: Hasil Dan Pembahasanunclassified
“…Stimulus dini begitu dibutuhkan anak selaku stimulus teruntuk aspek perkembangan mereka. Perihal terkait seringnya diabaikan oleh sejumlah orangtua sebab ketaktahuannya perihal langkah serta krusialnya pemberian stimulasi anak semenjak berusia dini (Abidah & Novianti, 2020).…”
Section: Pendahuluanunclassified